An Analysis of The Effectiveness of Waqf Fund Management Performance in Waqf Managing Institutions in Indonesia - Widiyanti, Dwi Retno; Abdurrahman, Anas Faqih; Hafidzuddin, Ihsan (Universitas Pendidikan Indonesia, 2024)
AbstractPurpose – The purpose of this research is to measure the efficiency of waqf funds managed by philanthropic institutions in Indonesia during the period 2018–2022. Four representations of best waqf funds institutions are chosen as sample, they are Dompet Dhuafa, Baitulmaal Muamalat, Waqf Al-Azhar, and Waqf Salman. Methodology - The method used is to use a quantitative approach using non-parametric Data Envelopment Analysis (DEA) data analysis techniques. The efficiency measurement is obtained from the using input variables (human resource costs, operational costs, and fixed assets) and output variables (collection and distribution of waqf funds).Findings - The Research findings show variations in the efficiency of waqf fund management between 2018 and 2022 that indicated the small impact of the COVID-19 pandemic on the efficiency of waqf institutions. Other findings revealed that Dompet Dhuafa has the most efficient DMU. It is qualified as the benchmark for other waqf institutions in their efforts to improve efficiency.Keywords: Efficiency; waqf institutions; Data Envelopment Analysis (DEA)